A function f is defned on the positive integers satisfies f ( 1 ) = 2 5 5 and i = 1 ∑ n f ( i ) = n 2 f ( n ) for n > 1
Find f ( 2 5 5 ) 1 .
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
i = 1 ∑ n f ( i ) = n 2 f ( n )
Replacing n by n + 1 ,
i = 1 ∑ n + 1 f ( i ) = n + 1 2 f ( n + 1 )
Subtracting above 2 equations and expanding the square,
n 2 f ( n ) = ( n 2 + 2 n ) f ( n + 1 )
Thus we have f ( n + 1 ) = n + 2 n f ( n ) (You could solve it using reccurence or by trying to find a pattern)
Putting n → n + 1
f ( n + 2 ) = n + 3 n + 1 ( n + 2 n f ( n ) )
Seeing the pattern:
f ( n + a ) = ∏ j = n + 2 n + a + 1 ∏ i = n n + a − 1 i f ( n )
\[f(n+a)=\frac{(n)(n+1)}{(n+a)(n+a+1)} f(n)
If n=1 and a=254
\[f(255)=\frac{(1)(2)}{(255)(256)} (255)\]
f ( 2 2 5 ) = 1 2 8 1
Thus our answer is 128
Problem Loading...
Note Loading...
Set Loading...
n 2 f ( n ) ( n 2 − 1 ) f ( n ) f ( n ) = f ( 1 ) + f ( 2 ) + f ( 3 ) + ⋯ + f ( n ) = f ( 1 ) + f ( 2 ) + f ( 3 ) + ⋯ + f ( n − 1 ) = ( n 2 − 1 ) f ( 1 ) + f ( 2 ) + f ( 3 ) + ⋯ + f ( n − 1 )
By using simple induction
f ( 1 ) f ( 2 ) = ( 2 2 − 1 ) f ( 1 ) = 3 f ( 1 ) f ( 3 ) = ( 3 2 − 1 ) f ( 2 ) + f ( 2 ) = 8 f ( 1 ) + 3 f ( 1 ) = 8 3 4 f ( 1 ) ⋯ f ( n ) = 2 5 5 = 2 ⋅ 3 2 f ( 1 ) = 3 ⋅ 4 2 f ( 1 ) = n ( n + 1 ) 2 f ( 1 )
then f ( 2 5 5 ) = 2 5 5 ⋅ 2 5 6 2 ⋅ 2 5 5 = 2 5 6 2
Answer = f ( 2 5 5 ) 1 = 1 2 8